2011
DOI: 10.1002/ajmg.b.32007
|View full text |Cite
|
Sign up to set email alerts
|

SNP variants within the vanilloidTRPV1andTRPV3receptor genes are associated with migraine in the Spanish population

Abstract: The transient receptor potential (TRP) superfamily of non-selective cationic channels are involved in several processes plausibly relevant to migraine pathophysiology, including multimodal sensory and pain perception, central and peripheral sensitization, and regulation of calcium homeostasis. With the aim of identifying single nucleotide polymorphisms (SNPs) in TRP genes that may confer increased genetic susceptibility to migraine, we carried out a case-control genetic association study with replication, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 51 publications
0
54
0
Order By: Relevance
“…Clinical trials with intranasal civamide (a synthetic capsaicin congener) TRP Channels as Drug Targets are now complete, but the results have not yet been disclosed (ClinicalTrials.gov identifiers NCT00069082 and NCT00033839). Preliminary studies suggest a link between migraine and TRPV1 variants (Carreño et al, 2012;Rainero et al, 2013).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical trials with intranasal civamide (a synthetic capsaicin congener) TRP Channels as Drug Targets are now complete, but the results have not yet been disclosed (ClinicalTrials.gov identifiers NCT00069082 and NCT00033839). Preliminary studies suggest a link between migraine and TRPV1 variants (Carreño et al, 2012;Rainero et al, 2013).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
“…However, it was suggested that polymorphism in the TRPV1 gene may play a role in the development and maintenance of chronic pain: indeed, genetic variants of human TRPV1 with M315I and I585V channel mutations were found in Caucasian patients with an increased individual susceptibility to neuropathic pain (Armero et al, 2012). SNPs in TRPV1 were also identified in a Spanish population with increased genetic susceptibility to migraine (Carreño et al, 2012). Interestingly, the M315I variant of the TRPV1 gene also conferred increased susceptibility (odds ratio of 1.6) to type 1 diabetes in Ashkenazi Jews (Sadeh et al, 2013).…”
Section: B Vanilloid Transient Receptor Potential Channelopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, initial studies investigating the possible association between TRP channels and human health and disease have so far shown a role for TRPV1. In a case-controlled study investigating 149 polymorphisms from 14 TRP channels, SNPs in TRPV1 and TRPV3 showed association with migraines in the Spanish population (5). In cough and airway diseases, the presence of the polymorphism TRPV1-I585V was recently found to be associated with a significantly reduced risk of cough in asthmatic children (6).…”
Section: Introductionmentioning
confidence: 99%
“…48,49 TRPA1 forms functional heterotetramers with TRPV1; hence variations in the TRPA1 gene may suggest functional deficits to TRPV1 that may not be related to polymorphism in nucleotides. 50 Importantly, Carreno et al 51 reported that TRPV1 contributes to the genetic susceptibility to migraine in a large study population of 500 Spanish participants, suggesting TRPA1 and TRPV1 may play a role in symptom presentation of CFS patients. Interestingly, analgesics and antinociceptive drugs target TRPV1 and TRPA1, respectively, to alleviate pain sensation [52][53][54] and these drugs are routinely prescribed to CFS patients.…”
mentioning
confidence: 99%